Evaluation of the chemical properties of labneh sold in some markets of Tripoli city (Comprehensive Journal of Science, 2025)
This study aimed to evaluate the chemical properties of labneh (concentrated yogurt) offered for sale in some shops (10 stores) located within the city of Tripoli during the period from September to October of the year 2023.analyses were conducted to estimate the percentage of acidity ,fat, relative humidity non-fat solids, and total solids for 30 labneh samples including (15) traditionally manufactured labneh samples preserved in oil and commercial labneh treated with heat after fermentation. The result of the study showed that the average percentage of acidity, fat ,moisture non-fat solids, and total solids for the samples of labneh preserved in oil were 1.24±0.20, 28.95±.2.68, 48.04±3.58, 23.06±3.71, 52.03±3.41, and for commercial labneh 0.45±0.08,18.91±1.23, 71.75±0.55, 9.31±0.90, 28.24±0.5 5respectively. All the labne samples under study were classified as full-fat as their fat content exceeded 10% according to Syrian standard specification No.(178) of 1978,and 12%,7% for labneh preserved in oil and heat-treated after fermentation ,respectively, according to gulf standard specification No.(816) of 2008. The average acidity percentages were
Keywords: : Labneh, chemical properties, characters Commercial, Homemade labenah, branded Labneh.